Predicting the sharing and reception of COVID-19-related information on social media - Aurelius Ratu; Endang Susilowati; Sukriyah Kustanti Moerad (Intelektual Pustaka Media Utama, 2022)
In a health crisis, social media is one of the primary means of disseminating and receiving information. Nevertheless, questions remain regarding what facilitates individual engagement in sharing or receiving information in the context of COVID-19, specifically for the Indonesian context. Analysis of a questionnaire survey among 255 from the random population of Indonesian showed that sharing information is predicted by gender and education. There was no significant relationship between social-demographic and receiving information. For psychosocial characteristics, personal risk perception predicted receiving information, while sharing information was predicted by societal risk perception. Societal risk perception and self-efficacy interacted with each other to predict the sharing of COVID-19-related information. One of the findings indicated a socio-cultural feature through which is considered to play an important role in personal and societal risk perception when sharing or expressing information. Given the benefits of social media communication during this pandemic, this study suggested that governments and policymakers should pay closer attention to a local community that is more effective in keeping everyone safe. Unfortunately, on another side, social media provides less information about narratives, storytelling, and empathy to maintain public trust.